Jonggan Dayak Kanayatn Dance: Study of Educational Values in The Learning Process in Elementary Schools - Mukhlisin, Mukhlisin; Hartono, Hartono; Lanjari, Restu (Catharsis, 2020)
The learning process is inseparable from the educational values that occurs during the learning and teaching activities taking place, and also in the learning process of Jonggan Dayak Kanayatn Dance. This study examined the educational value in the learning process of Jonggan Dayak Kanayatn Dance in elementary schools. This research used qualitative method and educational approach. Data collection used observation, interview and document study technique. Data analysis procedures used data reduction, data presentation and data verification. Analysis of the educational value in the learning process of Jonggan Dayak Kanayatn Dance used Rosyadi and Hasbullah Analysis. The validity of the data in this study used triangulation of data sources. The results of the study were: 1). Religious Value; 2). Discipline Value; 3). Responsibility Value; 4). Independence Value; 5). Tolerance Value and Hard Work Value. Specifically, the findings in the Jonggan Dayak Kanayatn Dance learning process, there was an educational value that is reflected in the Jonggan Dayak Kanayatn Dance learning process in Elementary Schools. The benefits of the results of this study can be used as a reference in dance learning in particular and in learning other arts in general.